STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN PRODUK - H. Abdul Rasul (Jurnal Bisnis dan Kewirausahaan, 2017)
In the context of the preparation of strategy, marketing has two dimensions, namely the current dimensions and dimension that will come. Current dimensions related to the relationship that has existed between the company and its environment. While the dimensions of the future include the relationship in the future is expected interwoven with courses of action necessary to achieve that goal. The marketing strategy drawn up would be tested in the implementation of the right to know or do not set it, This will be reflected and the level of sales, market share controlled and costs are sacrificed